STRATEGI PENGEMBANGAN TELUR AYAM KAMPUNG UNGGUL BALITBANGTAN (KUB) DI JOGJA AGROPARK, KULON PROGO, YOGYAKARTA - Nugraha, Maulana Adhika; Arsalina, Rara; Arupadatu, Sanca; Gayatri, Nanda Sekar; Amirullah, Amirullah; Dewi, Meita Puspa (Fakultas Pertanian, Universitas Janabadra, 2024)
This study aims to formulate a strategy for developing superior village chicken eggs of Balitbangtan (KUB) in Jogja Agro Park (JAP) Dusun Kemiri, Wijimulyo Village, Nanggulan District, Kulon Progo Regency, DIY. SWOT analysis was used to identify internal and external factors to formulate a strategy for developing KUB chicken eggs. The results showed that KUB chicken cultivation in JAP consisted of activities such as procuring DOC chicks, providing feed and drink, cleaning cages, vaccinations, collecting eggs, marketing eggs, and meat from retired KUB chickens (chickens that have reached the end of their productive period). KUB chicken cultivation in JAP uses a colony cage model with a total population of 14 male chickens and 146 female chickens with the ability to produce 30-40 eggs/day. The eggs produced are sold every Friday at the Farmer's Market for Rp2,300.00/egg using mica packaging containing 10 eggs. Retired chickens will be auctioned at the farmer's market for Rp30,000.00/kg alive. Based on the results of the SWOT analysis, a development strategy was obtained in the form of improving facilities and infrastructure, improving cage designs for laying hen farming, routine vaccination, and vitamin administration, increasing maintenance intensity, making alternative animal feed (independent), and expanding the marketing network for Kampung Unggul Balitbangtan (KUB) chicken eggs with social media.